2022
DOI: 10.1080/20008198.2022.2066457
|View full text |Cite
|
Sign up to set email alerts
|

Don’t get too close to me: depressed and non-depressed survivors of child maltreatment prefer larger comfortable interpersonal distances towards strangers

Abstract: Background Childhood maltreatment (CM) is frequently linked to interpersonal problems such as difficulties in social relationships, loneliness, and isolation. These difficulties might partly stem from troubles regulating comfortable interpersonal distance (CIPD). Objective We experimentally investigated whether CM manifests in larger CIPD and whether all subtypes of CM (i.e., physical, emotional, or sexual abuse and physical or emotional neglect) affect CIPD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Third, most of included studies used questionnairebased measures as the method of assessing social functioning and CM, which are subject to bias. 141 However, it is encouraging that there are new studies adopting assessments and application of experimental stimuli and settings that are close to real-life, such as interactive experimental paradigms with different interactions partners and contexts, 142,143 and virtual reality 144 environments. 145 Finally, more global representation is needed in the evidence base.…”
Section: Future Lines Of Researchmentioning
confidence: 99%
“…Third, most of included studies used questionnairebased measures as the method of assessing social functioning and CM, which are subject to bias. 141 However, it is encouraging that there are new studies adopting assessments and application of experimental stimuli and settings that are close to real-life, such as interactive experimental paradigms with different interactions partners and contexts, 142,143 and virtual reality 144 environments. 145 Finally, more global representation is needed in the evidence base.…”
Section: Future Lines Of Researchmentioning
confidence: 99%
“…1 ) should, i.a., focus on problems in the regulation of closeness and distance which might contribute to partnership conflict and reduced sexual and relationship satisfaction. It has recently been proposed that based on learning history, individuals exposed to CM show abnormal neural responses to social signals, such as facial expressions [ 76 ] or the perception of touch [ 77 ], which might result in discomfort in situations of physical proximity, and a preference for larger interpersonal distances [ 77 , 78 , 79 ]. In addition, future studies should try to identify alterations in communicative processes and behaviors that contribute to negative evaluation by others [ 51 ].…”
Section: Aims Of Future Researchmentioning
confidence: 99%
“…Research on the association between CM and CID is scarce. Using the stop-distance procedure, studies found an increased CID in physically abused children (Vranic, 2003) and adults with mixed types of CM (Maier et al, 2020;Lüönd et al, 2022. This finding was replicated by Lüönd et al (2022) and by Hautle et al (manuscript submitted for publication b), with mixed findings regarding the impact of depressive symptoms: Lüönd et al (2022) found that in adults with CM and symptoms of depression, all subtypes of CM were linked to a larger CID. In the absence of depressive symptoms, only adults exposed to emotional abuse showed an increased CID.…”
Section: Introductionmentioning
confidence: 85%
“…The complete absence of transcultural research and the lack of studies involving populations outside of Europe is problematic, given cultural and geographical effects on the processing of socio-emotional signals in general (e.g., Liddell & Williams, 2019;Matsumoto et al, 2010) and on CID in particular (Beaulieu, 2004;Evans et al, 2000;Ozdemir, 2008;Sorokowska et al, 2017). Finally, unlike other research on CID (e.g., Haim-Nachum et al, 2021), all of the previous studies on CID in CM have focused exclusively on CID towards strangers (Hautle et al, manuscript submitted for publication b;Lüönd et al, 2022;Maier et al, 2020;Vranic, 2003). It is thus unknown whether larger CID in individuals exposed to CM is restricted to strangers or extends to known others, as was found for individuals with high levels of social anxiety (Perry, 2013) and for individuals suffering from adjustment disorder with depressed mood (Ponizovsky et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation